A hybrid system approach for space station risk analysis. (1st January 2002) - Moynihan, Gary P.; Fonseca, Daniel J.; Ray, Paul S.
This paper describes a conceptual design for an integrated hybrid system for risk analysis applications on the International Space Station project. The expert system's knowledge base incorporates heuristics to integrate and interpret the algorithmic results from both simulation (for project risk analysis) and probabilistic risk assessment (regarding safety issues). This project was conducted in four phases: model base analysis, knowledge engineering, knowledge base design, and development of the functional system design. A functional system design document was developed in order to identify the detailed system architecture, processing considerations, and definition of displays and reports. Recommendation of software products was based on investigation of functionality, installation, and integration characteristics, as well as compatibility with existing NASA hardware, software, and communications investments. A prototype system was then developed.